2006
DOI: 10.1037/0002-9432.76.4.423
|View full text |Cite
|
Sign up to set email alerts
|

The Afghan Symptom Checklist: A culturally grounded approach to mental health assessment in a conflict zone.

Abstract: This article describes a methodology for developing culturally grounded assessment measures in conflict and postconflict situations. A mixed-method design was used in Kabul, Afghanistan, to identify local indicators of distress and develop the 22-item Afghan Symptom Checklist (ASCL). The ASCL contains several indigenous items and items familiar to Western mental health professionals. The ASCL was pilot tested and subsequently administered to 324 adults in 8 districts of Kabul. It demonstrated excellent reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
185
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(192 citation statements)
references
References 25 publications
(23 reference statements)
5
185
1
1
Order By: Relevance
“…This is consistent with previous studies which have reported a high prevalence of mental health concerns among former refugee groups. In particular, we noted significant differences between groups based on gender, with females scoring higher on the distress scale than males, which is also consistent with other research (Miller et al, 2006;Porter & Haslam, 2005;Schweitzer, Melville, Steel, & Lacherez, 2006). Unemployment, not being able to speak English, being previously married (either divorced or widowed), and having only minimal education were also associated with an increased risk of psychological distress as reported elsewhere (Beiser & Hou, 2001;Laban, Gernaat, Komproe, van der Tweel, & De Jong, 2005;Nwadiora & McAdoo, 1996).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with previous studies which have reported a high prevalence of mental health concerns among former refugee groups. In particular, we noted significant differences between groups based on gender, with females scoring higher on the distress scale than males, which is also consistent with other research (Miller et al, 2006;Porter & Haslam, 2005;Schweitzer, Melville, Steel, & Lacherez, 2006). Unemployment, not being able to speak English, being previously married (either divorced or widowed), and having only minimal education were also associated with an increased risk of psychological distress as reported elsewhere (Beiser & Hou, 2001;Laban, Gernaat, Komproe, van der Tweel, & De Jong, 2005;Nwadiora & McAdoo, 1996).…”
Section: Discussionsupporting
confidence: 80%
“…Majority group attitudes towards migrants, social exclusion, and perceptions of discrimination are especially relevant for visibly different groups like Muslims or Africans, and pose particular challenges to resettlement (Casimiro, Hancock, & Northcote, 2007). In particular, a high prevalence of mental health problems among Afghans and other refugee groups from the Middle East has been documented (Gerritsen et al, 2006;Hosin, Moore, & Gaitanou, 2006;Miller et al, 2006;Mofidi, Ghazinour, Araste, Jacobsson, & Richter, 2008;Taloyan, Johansson, Johansson, Sundquist, & Kocturk, 2006), which may manifest as behavioral shifts or lead to acculturative stress characterized by depression, anxiety, uncertainty, or dysphoria (Allen, Vaage, & Hauff, 2006;Berry, 2002). Although social support has been shown to enhance coping and promote health, (Ghazinour, Richter, & Eisemann, 2004;Oppedal, Roysamb, & Sam, 2004;Simich, Beiser, & Mawani, 2003) the involuntary nature of the refugee experience predisposes refugees to stress reactions.…”
mentioning
confidence: 99%
“…To address catastrophic cognitions, explanatory models or symptom descriptions used by the participants were used to enhance understanding; the treatment elicits patient understanding of symptoms, which allows this intervention. Prominent idioms of distress such as cultural syndromes and somatic symptoms gathered in advance were discussed in group (Alemi, James, & Montgomery, 2016; Miller et al, 2006; Yaser et al, 2016). Over the sessions participants were taught Yoga (stretching) exercises, and basic techniques of mindfulness.…”
Section: Methodsmentioning
confidence: 99%
“…Adaptations of the manual specific to the Afghan culture covered four dimensions:Perception and appraisal of symptoms: Among Farsi speakers, idioms of distress include ‘asabi’ (nervous agitation), ‘gham’ (sadness), and ‘jigar khun’ (expression often used to describe grief after the loss of family members or friends) (Miller et al, 2006). Depression is often described as ‘thinking too much’ (ruminative sadness), ‘inability to perform daily tasks’, ‘abdominal pain’, ‘going crazy’, ‘goshagary’ (self-isolation), and ‘dementia’ (Alemi et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The physical and mental health components of the ShortForm/SF-8 [17] were used to provide a measure of health-related quality of life (HR-QoL). The choice of this measure was partly based on Roberts' et al [18] We also measured psychological distress symptoms using a culturally-grounded measure of mental health developed in Afghanistan-the Afghan Symptom Checklist (ASCL) [20]. Items are based on a two-week recall period and are rated on a scale ranging from 1 ("never") to 5 ("everyday").…”
Section: Independent Variablesmentioning
confidence: 99%